2014
DOI: 10.1007/s10735-014-9584-1
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cancer stem cell marker during 4-nitroquinoline 1-oxide-induced rat tongue carcinogenesis

Abstract: One of the theories regarding oral carcinogenesis is that the tumor growth is initiated from cancer stem cells (CSCs) that self-renew and give rise to differentiated tumor cells, like stem cells do in normal tissues. The most common methods of CSC identification are based on CSC marker expression in carcinogenesis. This study examined the expression of CD133 and CD44, the most commonly used CSC biomarkers in oral squamous cell sarcoma (SCC), with the goal of identifying molecular biomarkers whose expression is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Also, CSCs share certain regulators with normal SCs. For example, SCC CSCs express factors that regulate self-renewal in embryonic SCs, such as SOX2, MYC, and OCT-4 (Bose and Shenoy, 2014; Boumahdi et al, 2014; Lim et al, 2014). Similarly, some common “stemness” pathways are activated in follicular SCs and CSCs, such as Wnt signaling (Malanchi et al, 2008; White et al, 2013).…”
Section: Scs Versus Scc Cscs In the Skinmentioning
confidence: 99%
“…Also, CSCs share certain regulators with normal SCs. For example, SCC CSCs express factors that regulate self-renewal in embryonic SCs, such as SOX2, MYC, and OCT-4 (Bose and Shenoy, 2014; Boumahdi et al, 2014; Lim et al, 2014). Similarly, some common “stemness” pathways are activated in follicular SCs and CSCs, such as Wnt signaling (Malanchi et al, 2008; White et al, 2013).…”
Section: Scs Versus Scc Cscs In the Skinmentioning
confidence: 99%
“…Furthermore, CD44 and CD133 expressions were found to be strongly overexpressed in 4-Nitroquinoline 1oxide induced TSCC in addition to several other cancer stem cell markers including ALDH1, Nanog and OCT-4. These findings point out the importance of CD44 as well as other cancer stem cell markers in the multistep carcinogenesis process of TSCC (Lim et al 2014).…”
Section: Cd44mentioning
confidence: 67%
“…CSCs were reported to be enriched in the highly invasive UM1 cell line which is strongly positive for CD44 expression but were not present in the less invasive UM2 cell line (Misuno et al 2013). In a recent study, where 4-Nitroquinoline 1-oxide was used to induce tongue cancer in mice, CD44 expression along with CD133 was found to be slightly overexpressed in dysplasia group compared to normal rats (Lim et al 2014). Furthermore, CD44 and CD133 expressions were found to be strongly overexpressed in 4-Nitroquinoline 1oxide induced TSCC in addition to several other cancer stem cell markers including ALDH1, Nanog and OCT-4.…”
Section: Cd44mentioning
confidence: 99%
“…Consequently, CD133 is considered an important cell surface marker for a subpopulation of cancer initiating cells (CICs) in brain tumors, colon carcinoma, head and neck cancer, hepatocellular carcinoma, thyroid carcinoma, and PC . Previously, we demonstrated that upregulation of CD133 on head and neck cancer cells and in head and neck squamous cell carcinoma tissue correlates with chemoresistance to anticancer drugs such as 5‐FU . Recent reports suggest that expression of CD133 by tumor tissues may be a prognostic indicator for tumor regrowth, malignant progression, and patient survival .…”
Section: Introductionmentioning
confidence: 98%
“…(14)(15)(16)(17) Previously, we demonstrated that upregulation of CD133 on head and neck cancer cells and in head and neck squamous cell carcinoma tissue correlates with chemoresistance to anticancer drugs such as 5-FU. (18,19) Recent reports suggest that expression of CD133 by tumor tissues may be a prognostic indicator for tumor regrowth, malignant progression, and patient survival. (20) Nevertheless, the CD133mediated molecular mechanisms that regulate differentiation of osteocytes and osteoclasts during bone metastasis of PC remain unclear.…”
Section: Introductionmentioning
confidence: 99%